Cone, tetrahedron and unit interval - Azram, Mohammad (Sci.Int.(Lahore), 2012)
In this article we have established a bijection from a unit solid circular cone onto a family of subintervals of a unit interval with some notions. Consequently, the unit interval has been embedded into unit solid circular cone. Further, imposing a Hausdorff metric on family of subintervals of unit interval, we were able to convert the same bijection into a homeomorphis. We have also established a homeomorphism from unit solid circular cone onto a tetrahedron.